(untitled) (Journal of Society of Surgeons of Nepal, 2023)
Obturator hernia is an extremely rare type of hernia that presents with signs and symptoms of intestinal obstruction. Its early diagnosis is difficult because the signs and symptoms are non-specific. A 72-year-old woman was admitted to our hospital in the emergency ward with complaints of intermittent abdominal colicky pain, abdominal distension, and bilious vomiting from last six days. The abdomen skiagram showed an obstructed loop of the bowel in the pelvis. After initial resuscitation, an exploration of the abdomen was planned. The patient also had multiple ileal diverticula in the terminal ileum. The only treatment for the obturator hernia is surgery.